Peran Motivasi Belajar dalam Memediasi Pengaruh Penggunaan E-Learning dan Kemandirian Belajar terhadap Hasil Belajar - Genarsih, Tunjung; Tisngati, Urip (Jurnal Penelitian Pendidikan, 2023)
This study aims to see the partial effect of the use of e-learning and independent learning on the learning outcomes of introductory economics and business statistics with motivation as a mediator. The type of research used is quantitative with a survey method. Samples were taken using the Slovin formula and obtained as many as 96. The analysis used was path analysis. The research results obtained include; 1) the use of e-learning has a significant effect on motivation because the value of sig. 0.000; 2) learning independence has no significant effect on motivation with sig. 0.645; 3) the use of e-learning has a significant effect on learning outcomes with sig. 0.007; 4) learning independence has a significant effect on learning outcomes with sig. 0.000; 5) motivation has a significant effect on learning outcomes with sig. 0.000; 6) learning motivation can mediate the effect of using e-learning on learning outcomes with a value of Z = 4.89; 7) learning motivation cannot mediate the influence of independent learning on learning outcomes with a value of Z = 0.4572. Further research still needs to be done using other relevant variables.